Adapting Henry James to the screen: Washington Square & The portrait of a lady - Mowlana, Yasmin (Department of English Language and Literature, 2023)
This dissertation explores the film adaptations of two of the novels of Herny James, namely Washington Square (1880) and The Portrait of a Lady (1881). The Introduction discusses issues relating broadly to the problems and attractions of film adaptation. I draw especially on the work of James Naremorc, Brian Mcfarlane and George Bluestone. Naremore surveys the history of film adaptation, pervasive in many countries with a film industry. Mcfarlane looks at the reasons for this interest in adapting novels to film as well as the issue of authenticity with regard to film adaptation. Bluestone looks at what film and literature have in common. In Chapter One, I discuss the novel Washington Square and two adaptations, William Wyler's 1949 version and Agnieszka Holland's 1997 version. The chapter opens with a discussion of the novel, focussing on themes such as marriage, money and status in society. I then examine selected aspects of the two films. In The Heiress, I look at the inclusion of scenes that don't appear in the novel, and how these scenes drive the narrative in the film. I also look at how the characters are portrayed in the film and how they bring their own uniqueness to the screen. In Holland's Washington Square, I examine both the characters and the sets, while also looking at Holland's feminist interpretation of the story. In Chapter Two, I examine the novel The Portrait of a Lady and Jane Campion's film version of this story. The discussion of the novel looks at themes like tragedy, the European experience, marriage, and the displaced American. I also discuss the various characters in the novel and the role that each of them plays. With regard to Campion's film, I look at unusual filmic devices that have been used as well as the way in which the characters from the novel have been translated to the screen. I conclude by noting how films have inspired people to read classic works once again.